An efficient CuI/DBU-catalyzed one-pot protocol for synthesis of 1, 4-disubstituted 1, 2, 3-triazoles. Issue 111 (18th November 2016) - Jiang, Yuqin; Li, Xingfeng; Zhao, Yaru; Jia, Shuhong; Li, Mingrui; Zhao, Zhiqi; Zhang, Ruili; Li, Wei; Zhang, Weiwei
Abstract : A convenient CuI/DBU catalyzed one-pot method has been developed for the synthesis of 1, 4-disubstituted 1, 2, 3-triazoles from aryl iodides, sodium azide and phenylacetaldehyde derivatives or from aryl iodides, sodium azide and alkynes in DMSO. Abstract : A convenient CuI/DBU catalyzed one-pot method has been developed for the synthesis of 1, 4-disubstituted 1, 2, 3-triazoles through the coupling of aryl iodides with sodium azide, followed by the intermolecular cyclization between the generated aryl azides and phenylacetaldehyde derivatives or alkynes in DMSO. The established protocol was compatible with a wide scope of substrates in good to excellent yields.